2023
DOI: 10.1177/11786302231151538
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Related to Heatwaves in Dezful City, Southwest of Iran

Abstract: Background: We aimed to evaluate the impact of heatwaves on daily deaths due to non-accidental, cardiovascular and respiratory causes in the city of Dezful in Iran from 2013 to 2019. Method: We collected daily ambient temperature and mortality and defined 2 types of heatwaves by combining daily temperature ⩾90th in each month of the study period or since 30 years with duration ⩾2 and 3 days. We used a distributed lag non-linear model to study the association between each type of heatwave definition, and deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…[ 3 4 ] These increases in heat currently have significant and costly effects on community health. [ 2 5 6 7 ] Some studies have shown the harmful effects of heat and heat waves on health. [ 5 8 9 10 ] With the frequent occurrence of heat weather, the prevalence of diseases, the rate of hospitalization, and mortality related to the weather will increase significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3 4 ] These increases in heat currently have significant and costly effects on community health. [ 2 5 6 7 ] Some studies have shown the harmful effects of heat and heat waves on health. [ 5 8 9 10 ] With the frequent occurrence of heat weather, the prevalence of diseases, the rate of hospitalization, and mortality related to the weather will increase significantly.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 5 6 7 ] Some studies have shown the harmful effects of heat and heat waves on health. [ 5 8 9 10 ] With the frequent occurrence of heat weather, the prevalence of diseases, the rate of hospitalization, and mortality related to the weather will increase significantly. These conditions indicate that heat weather is an important risk factor for human health.…”
Section: Introductionmentioning
confidence: 99%